Application-based remote interstage home monitoring for infants with shunt- or duct-dependent pulmonary perfusion - Rosenthal, Lisa-Maria; Danne, Friederike; de Belsunce, Sophie; Spath, Lisa; Badur, Chiara-Aiyleen; Photiadis, Joachim; Berger, Felix; Schmitt, Katharina (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveInterstage home monitoring (IHM) programs are considered standard of care after Norwood palliation and have led to substantial improvements in clinical outcomes. This study aims to evaluate an application-based remote IHM program for infants with shunt- or duct-dependent pulmonary circulation. The primary goals were to discharge infants from the hospital while minimizing mortality, optimizing somatic growth, and enhancing caregivers' confidence in the clinical management at home.MethodsInfants with shunt-dependent single ventricle physiology or complex biventricular physiology requiring staged palliation with aortopulmonary shunt were enrolled for the study. Caregivers completed a comprehensive education program on the clinical management of their child at home and were asked to remotely send monitoring data using an application. We analyzed demographic data and clinical outcomes; evaluated patient acceptance and adherence, as well as data entry patterns and metrics; and compared these to a historical control group monitored in a non-remote IHM program and with a propensity score-matched cohort adjusted for baseline characteristics.ResultsWe enrolled 30 infants in the remote IHM program between July 2021 and May 2024. The median duration of IHM was 110 days (IQR 75–140). A median of 353 (IQR 351–743) data entries were sent per patient during IHM of which 0.8% (IQR 0.3–1.9) were pathological. Readmissions (63%) and interventions (57%) were common, mainly due to cyanosis and infections. As all infants survived stage II palliation, interstage mortality could be reduced to 0% compared to 10.3% in the historical control group and was significantly lower compared to the propensity score-matched cohort with 14% (P = 0.032).ConclusionApplication-based remote IHM for infants with duct- or shunt-dependent pulmonary perfusion is feasible, with high acceptance and adherence. The program significantly reduced interstage mortality compared to traditional monitoring methods. Remote patient monitoring (RPM) improves communication between caregivers and healthcare teams, allowing for early intervention and optimized patient outcomes. RPM has the potential to improve outcomes, enhance patient safety, and reduce family burden in this high-risk population.